A detailed study of intermolecular interactions, electronic and vibrational properties of the metal complex bis(uracilato)diammine copper(ii) dihydrate - Gramajo Feijoo, Marcelo Eduardo (2018)
The aim of this work is to evaluate the vibrational, electronic and structural properties of [Cu(uracilato-N1)2 (NH3)2]2H2O complex. Density Functional Theory (DFT) calculations have been performed to investigate the geometric and electronic structure, and electronic absorption spectrum for the [Cu(uracilato-N1)2 (NH3)2]2H2O complex. In addition, a complete analysis of the normal modes of vibration of the metal complex has been performed using the experimental IR and Raman spectra. The theoretical geometrical parameters obtained by DFT calculations are in very good agreement with the experimental ones obtained by X-ray diffraction methods. A careful study of the intermolecular interactions observed in solid state was performed by using the Hirshfeld surface analysis and their associated 2D fingerprint plots. These results indicate that the crystal packing is stabilized by N-H???O hydrogen bonds interactions and π-stacking. In addition, C-H???π interactions have been observed.Time-dependent density functional theory (TD-DFT) methods employed to investigation the electronic transitions give insights into the optical transition involved in the excitation process. From our calculation results, all of the low-lying electronic states has characterized as a mixture of intraligand charge transfer (ILCT) and ligand to metal charge transfer (LMCT) in character.Finally, we have studied the interactions between nitrogen lone pairs of the ligands and antibonding d-type orbitals and intramolecular interactions in the coordination sphere by means the Natural Bond Orbital (NBO) and Atoms in Molecule (AIM) analysis.